ENERGY VALUE OF DIETARY INTAKE AND ITS CONFORMITY TO DAILY NEEDS IN YOUNG PEOPLE - Kolinko, L.M.; Vesnina, L.E. (World of Medicine and Biology, 2020)
The paper presents the energy value of dietary intake of people with different body weight and its compliance with daily energy needs. 96 people of both gender aged 18-25 have been involved into the study. In the groups with normal body weight, overweight (body mass index of 25.00-29.99 kg/m2) and Class I obesity (body mass index of 30.00-34.99 kg/m2) nutritional status has been studied by the method of 24-hour nutrition reproduction, as well as basal metabolism and recommended daily energy dietary intake. The energy value of the dietary intake of the subjects of both gender with overweight and Class I obesity significantly exceeded the energy value of the dietary intake of controls. In the group with overweight, the level of positive energy balance in male subjects on a weekday was 16.02%, in male subjects and female subjects on a weekend day was 26.47% and 24.46%, respectively. In male subjects with obesity, the level of positive energy balance on a weekday was 20.09%, on a weekend day was 33.92%, whereas in female subjects with obesity it was 10.48% and 37.28% on a weekday and a weekend day, respectively. Strong to moderate correlation has been established between anthropometric and energy metabolism values.